2018
DOI: 10.1192/bjp.2018.23
|View full text |Cite
|
Sign up to set email alerts
|

Artistic creativity and risk for schizophrenia, bipolar disorder and unipolar depression: a Swedish population-based case–control study and sib-pair analysis

Abstract: Students of artistic subjects at university are at increased risk of developing schizophrenia, bipolar disorder and unipolar depression in adulthood.Declaration of interestNone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 26 publications
3
31
0
1
Order By: Relevance
“…In a large Swedish cohort, teenagers who chose to study ‘core’ artistic subjects (subjects that involved ‘creation of art,’ such as visual arts) had a stronger correlation with a future hospitalization for schizophrenia compared to those that chose artistic subjects that place more emphasis on interpretation (e.g. dance) …”
Section: Evolutionary Theories Linking Schizophrenia To Adaptive Traitsmentioning
confidence: 99%
“…In a large Swedish cohort, teenagers who chose to study ‘core’ artistic subjects (subjects that involved ‘creation of art,’ such as visual arts) had a stronger correlation with a future hospitalization for schizophrenia compared to those that chose artistic subjects that place more emphasis on interpretation (e.g. dance) …”
Section: Evolutionary Theories Linking Schizophrenia To Adaptive Traitsmentioning
confidence: 99%
“…The study also showed the converse pattern of performance on the same in patients The third approach is that of case series studies on psychiatric groups of interest whose information processing deficits are believed to be of especial relevance to creative cognition. Disorders that have received most of the focus so far are bipolar disorder (Andreasen, 2008;Santosa et al, 2007;Soeiro-de-Souza, Dias, Bio, Post, & Moreno, 2011;Taylor, 2017) and schizophrenia (Abraham, Windmann, McKenna, & Güntürkün, 2007;Acar, Chen, & Cayirdag, 2018), which is to be expected given the population based studies that indicate a higher degree of these disorders of psychosis in relation to creative professions (Kyaga et al, 2013(Kyaga et al, , 2011MacCabe et al, 2018) as well as a modest genetic propensity for the same (Power et al, 2015) (also see Keller & Visscher, 2015). Other disorders of interest, which have albeit received comparatively little attention, include attention deficit hyperactivity disorder (ADHD) (Abraham, Windmann, Siefen, Daum, & Güntürkün, 2006;Boot, Nevicka, & Baas, 2017;Healey & Rucklidge, 2006), autism (Craig & Baron-Cohen, 1999;Diener, Wright, Smith, & Wright, 2014;Kasirer & Mashal, 2014) and dyslexia (Kasirer & Mashal, 2016;von Károlyi, Winner, Gray, & Sherman, 2003;Wolff & Lundberg, 2002).…”
mentioning
confidence: 99%
“…Creative productivity and willingness to present one's own work in public may decrease during depressed episodes. Population‐based Swedish studies showed that although the study of artistic subjects in secondary or tertiary education was associated with a higher risk of both, BD and unipolar depression (MacCabe et al, ), only people with BD were found to be overrepresented in artistic professions (Kyaga et al, ). Not surprisingly, participants of our study reporting increased activity associated with mood swings scored comparably high on the CAQ.…”
Section: Discussionmentioning
confidence: 99%